Managing ciprofloxacin-clozapine interaction with immunoassay-based monitoring: A case report - Kristin Waters, PharmD, BCPS, BCPP; Victoria Popielarz, BS, PharmD Candidate; Joseph Lumasag, BS, PharmD Candidate; Sara Wiesenfeld, BS, PharmD Candidate; Ashley Tewksbury, PharmD, BCPP (Mental Health Clinician)
Whereas the interaction between clozapine and ciprofloxacin is well-documented, this case report emphasizes the importance of closely monitoring clozapine plasma concentrations during concurrent administration. When available, clozapine concentrations may be obtained via immunoassay to assess clozapine concentrations more quickly and subsequently adjust clozapine doses. Frequent monitoring is especially important for guiding appropriate dose adjustments in the setting of patient-specific factors that may affect clozapine concentrations, such as change in smoking status, caffeine intake, and infection status. The case report focuses on a 57-year-old female hospitalized for abdominal wall cellulitis, which necessitated antibiotic therapy. The patient’s schizophrenia had been effectively managed with clozapine for several years. However, following the initiation of ciprofloxacin, she exhibited increased sedation and elevated clozapine plasma concentrations. Existing literature recognizes the interaction between ciprofloxacin and clozapine although no reports include corresponding clozapine plasma concentrations during a full course of ciprofloxacin. In this case, clozapine concentrations were drawn throughout the course of ciprofloxacin therapy using immunoassay technology, which has a quick turnaround time. This was especially helpful to guide dosing for this patient with a concurrent active infection and abrupt change in smoking status.